Dedifferentiated recurrent liposarcoma of the uterine corpus: A case report and literature review - Sana Mushtaq; Muhammad Arslan Ul Hassan; Yan Li; Ikran Abdi; Aqsa Ahmad; HaiNing Li (Case Reports in Women's Health)
Liposarcoma of the uterine corpus represents an exceptionally rare tumor, with few cases documented in the literature, underscoring its unique histopathologic characteristics and management challenges. This case describes the clinical management of a 57-year-old patient with well-differentiated liposarcoma of the uterine corpus who presented with a three-month history of abdominal pain and distension. She underwent an abdominal hysterectomy followed by chemotherapy but experienced local recurrence in the mesentery and retroperitoneum after 21 months. Tumor resection was performed again, followed by chemotherapy, but the patient experienced a second recurrence 15 months later, involving the small intestine, vaginal stump, and ureter, with evidence of dedifferentiated liposarcoma. A third surgical resection was carried out without administering chemotherapy and the patient remained asymptomatic at follow-up appointments every 3 months for a year. This case highlights the importance of acknowledging the aggressive nature of recurrent liposarcoma, especially its transition into dedifferentiated liposarcoma, and the need for tailored management strategies.